Determinants of Mountaineering Tourism Development Strategy at Gunung Slamet - Nawarini, Alisa Tri (Universitas Negeri Semarang, 2022)
During and after panedic COVID 19 attacked Indonesia, tourism sectior has fallen sharply. Adventure tourism is one of travel activities that considering save to do during this pandemic, especialy mountaineering activitiues. This research has the aims to analyze the influence of push factor and pull factor on mountaineering participation in Gunung Slamet. The research conducted to 90 climber whose climb to Gunung Slamet through Bambangan Gate in Purbalingga. The reults show that there is positive influence of push factor and pull factor to mountaineering participation in Gunung Slamet. This result can be recommnendation for Banyumas Government as administrator to develop promotional strategy through facility fullfillment for climber and increase use of social media to attract tourist